A Comparison of General Price Level and Historical Cost Financial Statements in the Prediction of Bankruptcy. - Norton, Curtis L.; Smith, Ralph E. (The Accounting Review, 1979)
ABSTRACT: The objective of this study is to compare the prediction of bankruptcy based on ratios computed from GPL financial statements to the prediction based on ratios computed from traditional historical cost financial statements. A sample of an equal number of bankrupt and non-bankrupt firms was chosen, and the financial statements were adjusted for the effects of general price level changes. Financial ratios were computed from both the traditional and GPL financial statements. Discriminant analysis was used for the bankruptcy classifications. The authors found that both GPL and traditional ratios exhibited the ability to predict bankruptcy. In spite of the sizable differences in magnitude that existed between GPL and historical cost financial statements, little difference was found in the bankruptcy predictions. GPL data were shown to be consistently neither more nor less accurate than historical data for predictions of bankruptcy.